Fabricating high mechanical strength γ-Fe2O3 nanoparticles filled poly(vinyl alcohol) nanofiber using electrospinning process potentially for tissue engineering scaffold. (July 2017) - Ngadiman, Nor Hasrul Akhmal; Mohd Yusof, Noordin; Idris, Ani; Kurniawan, Denni; Fallahiarezoudar, Ehsan
The use of electrospinning has gained substantial interest in the development of tissue engineering scaffolds due to its ability to produce nanoscale fibers which can mimic the geometry of extracellular tissues. Besides geometry, mechanical property is one of the main elements to be considered when developing tissue engineering scaffolds. In this study, the electrospinning process parameter settings were varied in order to find the optimum setting which can produce electrospun nanofibrous mats with good mechanical properties. Maghemite (γ-Fe2 O3 ) was mixed with poly(vinyl alcohol) and then electrospun to form nanofibers. The five input variable factors involved were nanoparticles content, voltage, flow rate, spinning distance, and rotating speed, while the response variable considered was Young's modulus. The performance of electrospinning process was systematically screened and optimized using response surface methodology. This work truly demonstrated the sequential nature of designed experimentation. Additionally, the application of various designs of experiment techniques and concepts was also demonstrated. Results revealed that electrospun nanofibrous mats with maximum Young's modulus (273.51 MPa) was obtained at optimum input settings: 9 v/v% nanoparticle content, 35 kV voltage, 2 mL/h volume flow rate, 8 cm spinning distance, and 3539 r/min of rotating speed. The model was verified successfully by performing confirmation experiments. The nanofibers characterization demonstrated that the nanoparticles were well dispersed inside the nanofibers, and it also showed that the presence of defects on the nanofibers can decrease their mechanical strength. The biocompatibility performance was also evaluated and it was proven that the presence of γ-Fe2 O3 enhanced the cell viability and cell growth rate. The developed poly(vinyl alcohol)/γ-Fe2 O3 electrospun nanofiber mat has a good potential for tissue engineering scaffolds.